Effect of EPS (Earning Per Share) NPM (Net Profit Margin) and ROA (Return on Asset) on Share Prices (a Case Study of Banking and Cigarette Companies Listed in the LQ45 Index on the Indonesia Stock Exchange 2016-2019 Period) - Seskia Pietyana Dewi Senewe; Rasmawati Nurjanah; Risma Nurmayanti (Future Science, 2020)
Fundamental analysis is an approach that is often used in predicting stock price movements. In this research, the problem taken is how the influence of EPS, NPM, and ROA on stock prices of banking and cigarette companies are included in the LQ45 index for the period 2016-2019. The population in this study are banking and cigarette companies that are members of the LQ45 index. Sampling in this study was carried out using purposive sampling, amounting to 7 companies. Data analysis was performed by multiple linear regression analysis. The type and source of data used are secondary data in the form of complete financial reports for the 2012-2014 period. Hypothesis testing in this study uses linear regression with the help of SPSS version 25 software. The results of multiple linear regression analysis with independent variables, namely stock prices and the dependent variable, namely EPS, NPM and ROA, show that EPS (X1) has a positive effect on stock prices (Y). while NPM (X2) and ROA (X3) do not affect stock prices (Y). Based on the results of the determination coefficient table, the adjusted R2 value is 0.828. This means that the influence given by the independent variable to the dependent variable partially or simultaneously is 82.8%. This means that only the Earning Per Share variable affects stock prices. Because the higher the EPS value, the more investors will buy shares, of course, this is a good contribution for cigarette and banking companies